2018
DOI: 10.29140/jaltcall.v14n3.232
|View full text |Cite
|
Sign up to set email alerts
|

3D digital games, virtual worlds, and language learning in higher education: Continuing challenges in Japan

Abstract: Past research on digital games and virtual worlds suggests that these platforms provide multiple benefits for language learning, including positive effects on motivation and opportunities for authentic learner interaction. Despite this, adoption of these platforms in classrooms appears largely nonexistent. We provide a review of research on the use of games and virtual worlds in language learning and report on the results of a recent survey and series of interviews with university language teachers in Japan. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…The use of avatars also acts as a powerful communication medium for students as well as a way to develop higher‐order thinking skills, as described in the introduction. However, many students and teachers remain reluctant to use VW (Gallego et al ., 2016; Gregory et al ., 2015; Swier & Peterson, 2018). The present study attempts to evaluate concomitantly the relative contribution of various factors to the intention to use VW in education.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The use of avatars also acts as a powerful communication medium for students as well as a way to develop higher‐order thinking skills, as described in the introduction. However, many students and teachers remain reluctant to use VW (Gallego et al ., 2016; Gregory et al ., 2015; Swier & Peterson, 2018). The present study attempts to evaluate concomitantly the relative contribution of various factors to the intention to use VW in education.…”
Section: Discussionmentioning
confidence: 99%
“…It has to be emphasized that VW may become more user friendly for students and teachers when the benefits outweigh the efforts required to adopt this innovative approach (Swier & Peterson, 2018). Therefore, the present study is important in revealing the factors that interfere with or enhance preservice teachers' abilities to cope with any advanced technology while they are still students.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other challenges in implementing SG in post-secondary education, identified by Chan and Zary (2019), were limited time for teaching skills development, limited resources to deploy new teaching methods, and the lack of knowledge about SG as teaching tools. Swier and Peterson (2018) examined implementation of 3D SG in English language teaching in Japan and identified the availability and usability of computer resources as the main challenge. They also found that participants who implemented SG did so in secret because their peers’ perceived SG as having limited academic value.…”
Section: Literature Reviewmentioning
confidence: 99%